3D visualisations for communicative urban and landscape planning: What systematic mapping of academic literature can tell us of their potential? - Eilola Salla; Jaalama Kaisa; Kangassalo Petri; Nummi Pilvi; Staffans Aija; Fagerholm Nora (ELSEVIER, 2025)
Public participation and collaboration supported by the opportunities that digital technologies offer are prolific themes in urban and landscape planning. In the past two decades, there has been a growing interest in the ca- pacity of 3D visualisations to support citizen and stakeholder engagement in communicative planning processes. However, the technical advances of 3D visualisations still outstrip the current understanding of their benefits, appropriate uses and usability in practical planning contexts. There are no reviews or systematic mapping of literature, to our knowledge, that investigate the available evidence on the usability of particular 3D visual- isations or that document the scope and gaps in current research on 3D applications in communicative planning. To answer this need we conducted a systematic mapping of academic literature reporting recent case studies of 3D visualisations that have been utilised or developed for communicative urban and landscape planning con- texts. We follow established guidelines for systematic reviews and used Scopus and Web of Science as primary electronic databases. Altogether, we reviewed 46 case studies globally. Our findings highlight the heterogeneity of planning contexts and purposes, terminology and technological 3D solutions. Moreover, the scarcity of real - life planning cases and robust and well-documented usability evaluations are evident in the literature. We discuss limitations of the existing academic literature for evidence-based understanding and suggest a common framework for reporting in the field of participatory and collaborative 3D visualisations to enable more rigorous and systematic evaluation of the usability and benefits of these technologies in urban and landscape planning.